2003
DOI: 10.1177/004051750307300905
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Analysis of Combined Heat and Water Vapor Transfer Through Clothes with Condensation

Abstract: A series of experiments is performed on the combined heat and water vapor transfer through fabric at simulated high altitudes. A considerable water vapor concentration difference is imposed between the water vapor source and the environment, so that condensation takes place in the specimen. A new analytical expression for the rate of condensation in textile materials is derived by considering the combined heat and mass transfer between the specimen and the environment. Although the amount of condensation in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Lotens, et al verified the essential correctness of their model by showing that computed results were in substantial agreement with three sets of data for human subjects who performed both light and heavy exercise while wearing either a semi-permeable or an impermeable outer garment. Fukazawa, et al (2003b) validated their model by showing that calculated mass fluxes were in good agreement with fluxes measured in a flat-plate apparatus (Fukazawa, et al, 2003a). Temperature, water vapour pressure, and total pressure (which affects the resistance to mass transfer) were varied over a considerable range of conditions.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Lotens, et al verified the essential correctness of their model by showing that computed results were in substantial agreement with three sets of data for human subjects who performed both light and heavy exercise while wearing either a semi-permeable or an impermeable outer garment. Fukazawa, et al (2003b) validated their model by showing that calculated mass fluxes were in good agreement with fluxes measured in a flat-plate apparatus (Fukazawa, et al, 2003a). Temperature, water vapour pressure, and total pressure (which affects the resistance to mass transfer) were varied over a considerable range of conditions.…”
Section: Introductionmentioning
confidence: 74%
“…While those variables are conceptually interesting, their practical utility is limited because they are not defined in terms of clothing properties and conditions on the skin and in ambient air. A conceptually elegant, but computationally demanding, analysis of moisture transport in clothing was described in 1986 by Farnworth, and a much simpler quasi-steady-state analysis was published in 1995 by Lotens, et al The approach developed by Lotens, et al was modified by Fukazawa, et al (2003b) to obtain an analytical solution, although the final result still appears to involve some computation. Both papers compare theoretical results with experimental data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By examining the rate of heat and moisture transfer through fabrics during steam exposure, and through understanding the mechanisms of such, differences among FR clothing materials can be evaluated and improved clothing systems can be developed. Although extensive research has been conducted to understand mechanisms of heat and vapour transfer through different clothing systems, most has focused on transfer from human skin towards the environment with relatively low heat fluxes [2,3,4,5,6,7]. Li [2] concluded that the transfer of energy in mostly porous textile assemblies was governed by conduction by air and fibers, convection and radiation, while moisture transfer mechanisms included vapour diffusion in void space, moisture absorption by fibers, evaporation, and capillary effects.…”
Section: Introductionmentioning
confidence: 99%
“…Fukazawa, Kawamura, Tochihara, et al [5] investigated the combined heat and water vapour transfer rate through clothes with condensation at simulated high altitudes; they found that the water vapour transfer rate was determined by the concentration gradient, while the saturation concentration was temperature dependent. Thus they concluded that the water vapour concentration and temperature gradient were the determinant factors in water vapour transfer and condensation in clothing.…”
Section: Introductionmentioning
confidence: 99%